Induction of lodging resistance in upland rice (oryza sativa L.) through mutagenesis - Jyothilekshmi S (Department of Plant Breeding and Genetics, Colllege of Horticulture, 2012)
An investigation was undertaken at College of Horticulture, Kerala Agricultural University during 2010-2012 to develop desirable mutants in rice varieties Swarna Prabha and Vaishak and to analyse the extent of variability generated as a result of induced mutagenesis. The experimental material consisted of two rice varieties Swarna Prabha (PTB 43) and Vaishak (PTB 60), suited for upland growing conditions and mutation induction was carried out using gamma rays as physical mutagen and EMS as chemical mutagen. Physical mutagenesis was carried out for in vivo studies and chemical mutagenesis was carried out for in vitro studies. For in vivo mutagenesis the optimum dose of mutagen was fixed by germination test and seedling vigour test. LD50 value was estimated by probit analysis and for variety Swarna Prabha lethal dose was obtained at 426Gy and for Vaishak it was fixed at 398Gy. Based on the lethal dose, two effective doses were selected for both the varieties. 400 Gy and 450 Gy doses were selected for Swarna Prabha and 375 Gy and 450 Gy doses were selected for Vaishak. M2 was raised following pedigree method and observations were noted so as to assess the extent of variability generated as a result of mutation induction. Significant amount of variability was noted for panicles per plant, panicle length and plant height. Panicles per plant, plant height and days to maturity recorded high values for heritability along with low genetic advance and hence selection will be rewarding only in later generations. Mutants performed better than the parents for characters such as panicles per plant, panicle length, grain yield per plant, days to maturity, and harvest index. Association studies for yield related characters revealed significant intercorrelation for all the characters. Simple correlation was worked out for lodging resistance and from this it was noted that cellulose content is having highly significant positive correlation with lodging resistance. Four mutants in Swarna Prabha (mutant lines 27, 43, 44 and 56) and eleven mutants in Vaishak (mutant lines 77,132,135,144, 151, 157, 158, 95,103,121 and 152) were found to be promising with better yield and lodging resistance. For in vitro studies using EMS as chemical mutagen, in vitro protocol was initially standardized. Effective sterilization was obtained when the seeds were treated first with 70 per cent alcohol for two minutes followed by treatment with 0.1 per cent mercuric chloride for two minutes. Variety Vaishak was found to have better response to in vitro culture than the variety Swarna Prabha. Callus induction media was standardized using different concentrations of 2,4-D and Kinetin and callusing response was found to be higher in MS media supplemented with 2 mg/l 2,4-D and 0.5mg/l Kinetin. Callus subculture was also carried out in the same media composition and regenerationmedia used was MS + 2.0 mg/l NAA + 0.5 mg/l BAP + 4.0 mg/l Kinetin. Mutagenesis was carried out on three week old subcultured calli with different doses of EMS for varying duration so as to estimate the LD50 value. Treated calli was transferred to regeneration media and the responses were marked as 25 per cent browning, 50 per cent browning, 75 per cent browning, 100 per cent browning and no browning. With increase in treatment concentration and duration the calli showed variation in its morphology. The calli which retained white colour were transferred to regeneration medium but due to the effect of duration and concentration of EMS treatment no further response was noted in the regeneration medium.